2011
DOI: 10.1096/fj.10-177527
|View full text |Cite
|
Sign up to set email alerts
|

Triggering of a novel intrinsic apoptosis pathway by the kinase inhibitor staurosporine: activation of caspase‐9 in the absence of Apaf‐1

Abstract: The protein kinase inhibitor staurosporine is one of the most potent and frequently used proapoptotic stimuli, although its mechanism of action is poorly understood. Here, we show that staurosporine as well as its analog 7-hydroxystaurosporine (UCN-01) not only trigger the classical mitochondrial apoptosis pathway but, moreover, activate an additional novel intrinsic apoptosis pathway. Unlike conventional anticancer drugs, staurosporine and UCN-01 induced apoptosis in a variety of tumor cells overexpressing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 50 publications
5
69
0
Order By: Relevance
“…The increased apoptosis appears to be at least partially p53 dependent (Figure 6b). Similar results were seen with the nongenotoxic agent staurosporine 36 ( Figure 6c and Supplementary Figure S7). TP8i cells also showed significantly higher activation of the executioner caspases 3/7 in response to both DOX and staurosporine in a p53+, but not p53i, background (Figure 6d).…”
Section: Resultssupporting
confidence: 83%
“…The increased apoptosis appears to be at least partially p53 dependent (Figure 6b). Similar results were seen with the nongenotoxic agent staurosporine 36 ( Figure 6c and Supplementary Figure S7). TP8i cells also showed significantly higher activation of the executioner caspases 3/7 in response to both DOX and staurosporine in a p53+, but not p53i, background (Figure 6d).…”
Section: Resultssupporting
confidence: 83%
“…This cell specificity of the noncanonical intrinsic apoptotic pathway may explain the previous controversial results on staurosporine-induced cell death, which were obtained with different cell lines and tissues. 11,37,38 Fetal thymocytes that lacked the canonical mitochondrial apoptotic pathway, and the cell lines derived from them, efficiently underwent caspase-dependent apoptosis by staurosporine treatment, which agrees with the observation that many apoptotic cells are present in Apaf-1-null E14.5 fetal thymus.…”
Section: Discussionsupporting
confidence: 83%
“…On the other hand, Stepczynska et al 37 suggested that a mitochondrial-independent pathway was responsible for staurosporine-induced apoptosis because a dominantnegative Caspase-9 cannot inhibit it. Manns et al 38 recently claimed that a noncanonical staurosporine-induced apoptosis pathway requires Caspase-9 but not Apaf-1. In this report, we showed that staurosporine could activate caspase-dependent apoptosis via two different intrinsic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed that AK-B knockdown in LCLs activated the internal apoptosis pathway through the activation of caspases 3 and 9. An internal apoptosis pathway activated via the cleavage of caspase 9 and 3 is well documented (74,75). Furthermore, previous studies also demonstrated that the mechanism behind caspase 3 activation and apoptosis (76)(77)(78) led to morphological and biochemical changes and the modification of key structural and regulatory proteins by caspase 3 (79,80).…”
Section: Discussionmentioning
confidence: 96%